The Management of the knowledge like educational process for the social transformation (Revista Electrónica REDINE, 2018)
The increasing conviction of which the education is the element key to generate substantial changes capablly of creating social transformations and of advancing towards the universalization of the rights, it has been allowed that the governments of the different countries should elaborate educational policies that break the traditional schemes of the educational process. In this respect, the school and the educational management play a very important paper to construct a just company, where the knowledge is an indicator of progress that it transforms to the company. For such a motive, this test is argued by theories and legal elements that allow to raise the need to generate innovative and creative theories in the managerial paradigm.
Keywords: knowledge management; education; social transformation